2006
DOI: 10.2337/dc06-0142
|View full text |Cite
|
Sign up to set email alerts
|

Low Blood Flow Estimates in Lower-Leg Arteries Predict Cardiovascular Events in Japanese Patients With Type 2 Diabetes With Normal Ankle-Brachial Indexes

Abstract: OBJECTIVE -To examine the association of baseline measures in lower-leg arteries and conventional cardiovascular risk factors with the incidence of cardiovascular disease (CVD) events in type 2 diabetic patients with normal ankle-brachial indexes (ABIs) (Ͼ0.9).RESEARCH DESIGN AND METHODS -We studied 129 type 2 diabetic patients and 35 age-matched nondiabetic subjects with no apparent CVD consecutively admitted to our hospital. At baseline, total flow volume and resistive index, as an index of vascular resistan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 37 publications
0
8
0
Order By: Relevance
“…The impairment of the elastic and muscular arteries in diabetes [25], resulting in poorly compressible vessels, which can increase the apparent ABI values [17]. There is a report that diabetic patients with ABI>0.90 had low blood flow in the lower-leg arteries [26], which suggested that measured ABI values might not reflect the actual condition of the peripheral arteries, particularly in diabetes. We might miss the patients with PAD if we adopt the current cutoff value of ABI 0.90 in diabetic patients.…”
Section: Discussionmentioning
confidence: 99%
“…The impairment of the elastic and muscular arteries in diabetes [25], resulting in poorly compressible vessels, which can increase the apparent ABI values [17]. There is a report that diabetic patients with ABI>0.90 had low blood flow in the lower-leg arteries [26], which suggested that measured ABI values might not reflect the actual condition of the peripheral arteries, particularly in diabetes. We might miss the patients with PAD if we adopt the current cutoff value of ABI 0.90 in diabetic patients.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that nondiabetic subjects had a typically triphasic waveform, which could be clearly separated into systolic and early and late diastolic phases of the cardiac cycle at popliteal artery [4,5]. Our waveform analyses showed diabetic patients to have lower systolic, late diastolic and total flow volumes at popliteal artery than those in nondiabetic subjects.…”
Section: Discussionmentioning
confidence: 48%
“…Total flow volume and flow components during the cardiac cycle at the popliteal artery were obtained. The instantaneous flow volume at 20 equally spaced time points through the cardiac cycle was calculated from the individual velocity images by integrating the velocity across the area of the vessel [4,5]. A resistive index, which reflects peripheral vascular resistance, has been defined as (A-B)/A, where A is the systolic peak velocity and B is the end-diastolic velocity [18].…”
Section: Image Analysis and Calculationsmentioning
confidence: 99%
See 1 more Smart Citation
“…It seems that these patients had a high occurrence of cardiovascular events in this study. These results are reported to be dependent on the study population, with the range between 10%–22% during patient follow-up (Booth et al 2006; Yoshimura et al 2006; Wilcox et al 2007). It is of note that cardiovascular event increases up to 50% in those who had suffered from myocardial infarction (Murcia et al 2004).…”
Section: Discussionmentioning
confidence: 99%